2013
DOI: 10.1002/cbdv.201200204
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxicity of Secondary Metabolites Isolated from Flourensia oolepis S.F.Blake

Abstract: The aim of this study was to isolate the active principles of Flourensia oolepis S.F.Blake (Asteraceae), which completely inhibited the germination of Raphanus sativus seeds at 10 mg/ml. Flavanone pinocembrin and sesquiterpene ilicol, were isolated by bioassay-guided fractionation. They were active both against monocot and dicot seeds. Pinocembrin was the most active compound, with an IC50 (germination) value of 0.24, 3.40, 3.28, and 3.55 mM against Panicum miliaceum, Avena sativa, Lactuca sativa, and R. sativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Apart from natural extraction, pinocembrin has been successfully biosynthesized [714] and chemosynthesized [15]. In pharmacological studies, it has shown a variety of properties that could hold promise for treating diseases such as endotoxin shock, cancer, and cardiovascular diseases [16].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from natural extraction, pinocembrin has been successfully biosynthesized [714] and chemosynthesized [15]. In pharmacological studies, it has shown a variety of properties that could hold promise for treating diseases such as endotoxin shock, cancer, and cardiovascular diseases [16].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent paper, we have demonstrated that its natural occurrence is restricted only to some Flourensia species, strictly FC, FO and F. fiebrigii, being absent in F. hirta, F. riparia and F. niederleinii, and in 37 of the most representative co-occurring species of FC and FO [15]. The composition of the resins from the genus Flourensia has revealed the presence of other phytotoxic compounds, as in F. cernua [16] and in FO [17]- [19]. Other resin components in Flourensia spp.…”
Section: Introductionmentioning
confidence: 99%
“…Since there is no common pharmacophore determining that a compound behaves as a P-gp reverser (Yuan et al, 2012) and due to the wide diversity of chemical structures that interact with this transporter (Robert and Jarry, 2003) as well as the lack of information on metabolites from Argentinian flora as P-gp chemosensitizers, we decided to investigate this effect in 15 plant-derived compounds belonging to different chemical families obtained from plants from central Argentina (Carpinella et al, 2002, 2003, 2005; Diaz Napal et al, 2009; Chiari et al, 2010, 2011; Joray et al, 2011, 2013, 2015; del Corral et al, 2012; Diaz Napal and Palacios, 2013). Compounds 1–15 were studied by an MTT assay, in order to evaluate the potentiation of DOX cytotoxicity in insensitive Lucena 1 cells, which were 35-fold more resistant to this drug [IC 50 = 40.78 (16.60–100.18) μM] than their parental cell line K562 [IC 50 = 1.16 (0.52–2.58) μM].…”
Section: Resultsmentioning
confidence: 99%
“…They were tested at 90% or higher purity, determined by HPLC. The compounds assayed were: vanillin ( 1 ) and, 4-hydroxy-3-methoxycinnamaldehyde ( 2 ), both isolated from Melia azedarach (Carpinella et al, 2003), ilicol ( 3 ) isolated from Flourensia oolepis (Diaz Napal and Palacios, 2013), scopoletin ( 4 ) obtained from M. azedarach (Carpinella et al, 2005), ( Z,Z )-5-(trideca-4,7-dienyl)-resorcinol ( 5 ) isolated from Lithrea molleoides (Carpinella et al, 2011), 2′,4′-dihydroxychalcone ( 6 ) and (-)-pinocembrin ( 7 ) both obtained from F. oolepis (Diaz Napal et al, 2009; Joray et al, 2015), naringenin ( 8 ) isolated from Baccharis salicifolia (Céspedes et al, 2006; del Corral et al, 2012), dalenin ( 9 ) obtained from Dalea elegans (Chiari et al, 2011), apigenin ( 10 ) isolated from B. salicifolia (del Corral et al, 2012), quercetin ( 11 ), 3- O -methylquercetin ( 12 ), and 23-methyl-6- O -desmethylauricepirone ( 13 ) obtained from Achyrocline satureioides (Joray et al, 2011, 2013) and (±)-pinoresinol ( 14 ) and meliartenin ( 15 ) both obtained from M. azedarach (Carpinella et al, 2002, 2003). 1-acetoxy-(+)-pinoresinol ( 16 ) (Figure 1) was purchased from Chem Faces (Wuhan, PR).…”
Section: Methodsmentioning
confidence: 99%